2019
DOI: 10.1136/bmjopen-2018-025531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of native language on CPR skills and willingness to intervene in out-of-hospital cardiac arrest after film-based basic life support training: a subgroup analysis of a randomised trial

Abstract: ObjectivesThe aim was to investigate whether the students’ native language, Swedish as native language (SNL) versus other native language (ONL), affects cardiopulmonary resuscitation (CPR) skills or willingness to act after film-based training in Swedish.Setting13-year-old students in two municipalities.DesignA subgroup from a previous randomised study was analysed. During 2013 to 2014, a film-based CPR method was evaluated. Practical skills and willingness to act were assessed directly after training and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 33 publications
2
26
0
6
Order By: Relevance
“…This was supported by the lack of knowledge of these participants, as less than half of them knew where to check correctly for pulsation and a little more than half knew the indication for Heimlich maneuver. Similar lack of knowledge was found in a study in Sweden which demonstrated that students scored up to 67% directly after training, and up to 61% at 6 months [10] .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This was supported by the lack of knowledge of these participants, as less than half of them knew where to check correctly for pulsation and a little more than half knew the indication for Heimlich maneuver. Similar lack of knowledge was found in a study in Sweden which demonstrated that students scored up to 67% directly after training, and up to 61% at 6 months [10] .…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, it demonstrated that most students (up to 85%) who received CPR training were willing to perform CPR on a friend but were less willing to perform it on a stranger (up to 52% after training). This percentage, however, has come down to 31% at 6 months [10] . A study in Saudi Arabia, demonstrated that overall positive attitudes of healthcare professionals to perform CPR were seen in 53.4% of pre-training respondents and 64.8% of post-training respondents [19] .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…EMS providers should be prepared when responding to emergency calls involving patients with limited language proficiency [33]. A recent study found that the use of language might have an effect on CPR skills and willingness to intervene in OHCA [34]. Although Mandarin is the official language in Taiwan, more than 80% of Taiwanese people can speak both Mandarin and Hokkien, a Taiwanese traditional language, fluently [35].…”
Section: Discussionmentioning
confidence: 99%
“…7,25 To compensate for disadvantages, the provision of training materials with subtitles and in different languages are recommended. 7,25 There are differences between age groups 7,16,23,42 and schoolchildren of different sexes. 4,7,23,27,33 A second barrier is the large difference in the willingness to perform CPR depending on the victim's characteristics.…”
Section: Resultsmentioning
confidence: 99%